Viral Agents Causing Acute Respiratory Infections in Children under Five: A Study from Eastern India - Pravakar Mishra; Lipika Nayak; Rashmi Ranjan Das; Bhagirathi Dwibedi; Amitabh Singh (Hindawi Limited, 2016)
Background. Acute respiratory infections (ARIs) are important cause of mortality and morbidity in children under five in developing country. Methods. This observational study was conducted over two-year period in a tertiary care teaching hospital of Eastern India. Nasal and throat swabs were collected, transported to the laboratory at 2-8°C in viral transport media, and then processed for detection of viruses using mono/multiplex real-time polymerase chain reaction. Results. A total of 300 children aged 2-60 months with ARIs were included. The most common age group affected with LRI was 2-12 mo and with URI was >12-60 mo. Viruses were detected in 248 cases. In URI, 77 were positive for single virus and 19 were positive for more than one virus; in LRI, 113 were positive for single virus and 12 were positive for more than one virus. The most common viruses isolated from URI cases were rhinovirus and adenovirus. The most common viruses isolated from LRI cases were respiratory syncytial virus and influenza virus. Most cases occurred in the months of January, December, and August. Conclusion. Viruses constitute a significant cause of ARI in children under five. RSV, ADV, RV, and IFV were the most prevalent viruses isolated.